2007
DOI: 10.2337/dc07-1110
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Administration Counteracts Oxidative Imbalance and Advanced Glycation End Product Formation in Type 2 Diabetic Patients

Abstract: OBJECTIVE -Dehydroepiandrosterone (DHEA) has been shown to prevent oxidative stress in several in vivo and in vitro models. This study aimed to evaluate the effects of DHEA administration on oxidative stress, pentosidine concentration, and tumor necrosis factor (TNF)-␣/ TNF-␣ receptor system activity in patients with type 2 diabetes.RESEARCH DESIGN AND METHODS -Twenty patients were enrolled in the study and randomly assigned to the DHEA (n ϭ 10) or placebo (n ϭ 10) group. Twenty healthy sexand age-matched subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…The use of many herbal medicines and experimental drugs has shown a reduction of AGE accumulation [49][50][51][52][53][54][55][56]. Also, many conventional drugs are useful in the reduction of AGE.…”
Section: Use Of Advanced Glycation End-products Reducing Drugsmentioning
confidence: 99%
“…The use of many herbal medicines and experimental drugs has shown a reduction of AGE accumulation [49][50][51][52][53][54][55][56]. Also, many conventional drugs are useful in the reduction of AGE.…”
Section: Use Of Advanced Glycation End-products Reducing Drugsmentioning
confidence: 99%
“…We recently showed that free-radical overproduction appears early in human type 2 diabetes (Brignardello et al 2007) and that, in a rat model of type 1 diabetes, oxidative damage plays a key role in the early development of cardiomyopathy (Aragno et al 2006). Antioxidants might counteract insulin resistance associated with type 2 diabetes and cardiovascular diseases (Robertson 2006;Davì et al 1999;Minamiyama et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…We reported elsewhere that, in streptozotocin (STZ) rats, treatment with DHEA, prevents myocardial damage induced by oxidative stress, while avoiding impairment of cardiac myogenic factors and the switch to myosin heavy-chain expression (Aragno et al 2008). DHEA also counteracts oxidative imbalance and advanced glycation end-product (AGE) formation in type 2 diabetic patients (Brignardello et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Among steroids with beneficial effects on both of these undesired conditions, the preventive effects of dehydroepiandrosterone (DHEA) and estradiol, both candidates for steroid replacement therapy, should be mentioned here [42][43][44].…”
Section: Ad As Diabetes Mellitus Type III and The Role Of Steroidsmentioning
confidence: 99%